Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1097/inf.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability and Immunogenicity of 15-valent Pneumococcal Conjugate Vaccine in Toddlers Previously Vaccinated With 7-valent Pneumococcal Conjugate Vaccine

Abstract: Both formulations of PCV15 display acceptable safety profiles and induce IgG and OPA responses to all vaccine serotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…79 Our included studies summarized in the current analysis confirmed that serotype 14 was the most common serotype in African children. 80 The two vaccines provided coverage for 66.9% % and 80.6% of serotypes detected in IPD, respectively The proposed PCV15, which adds serotypes 22F and 33F, 81 would provide coverage against only an additional 0.11% of circulating strains compared with PCV13. Surprisingly, PCV13 was found to cover a higher proportion (98.6%) of serotypes causing nonbacteremic pneumonia/noninvasive disease, compared to IPD (80.6%).…”
Section: Discussionmentioning
confidence: 99%
“…79 Our included studies summarized in the current analysis confirmed that serotype 14 was the most common serotype in African children. 80 The two vaccines provided coverage for 66.9% % and 80.6% of serotypes detected in IPD, respectively The proposed PCV15, which adds serotypes 22F and 33F, 81 would provide coverage against only an additional 0.11% of circulating strains compared with PCV13. Surprisingly, PCV13 was found to cover a higher proportion (98.6%) of serotypes causing nonbacteremic pneumonia/noninvasive disease, compared to IPD (80.6%).…”
Section: Discussionmentioning
confidence: 99%
“…Five independent laboratories participated in bridging the serotype-specific IgG assignments for 89SF to the new reference standard, 007sp, to establish equivalent reference values for 13 pneumococcal capsular serotypes (1,3, 4, 5, 6A, 6B, 7F, 9V, 14, 18C, 19A, 19F, and 23F) by using the WHO reference ELISA (3). 007sp has replaced 89SF (which is no longer distributed) and been routinely used in pneumococcal assays globally since 2011.With the ongoing requirement to evaluate Pneumovax II and the ongoing development of additional extended valency conjugate vaccines, it has been imperative to assign values to 007sp for additional serotypes (4,5). This report describes the efforts undertaken to establish the serotype-specific IgG concentrations for 007sp to seven more serotypes (8, 10A, 11A, 12F, 15B, 22F, and 33F), to validate its performance as a standard, and to assign values to a set of 12 existing World Health Organization (WHO) quality control (QC) serum samples for the serotypes.…”
mentioning
confidence: 99%
“…With the ongoing requirement to evaluate Pneumovax II and the ongoing development of additional extended valency conjugate vaccines, it has been imperative to assign values to 007sp for additional serotypes (4,5). This report describes the efforts undertaken to establish the serotype-specific IgG concentrations for 007sp to seven more serotypes (8, 10A, 11A, 12F, 15B, 22F, and 33F), to validate its performance as a standard, and to assign values to a set of 12 existing World Health Organization (WHO) quality control (QC) serum samples for the serotypes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…6 Serotype 33F is included in a 15-valent conjugate vaccine currently in trial. 9 Both 15B and 33F are included in the 23-valent pneumococcal polysaccharide vaccine but this vaccine is not currently recommended for children without underlying medical conditions and is not intended to replace conjugate vaccines. 10 The large number of pneumococcal serotypes, and the possibility for even lessinvasive serotypes such as 15B to produce invasive disease as in patient 2, also provide support for alternative vaccination strategies that are not serotype-specific.…”
mentioning
confidence: 99%